2022
DOI: 10.3390/su142417008
|View full text |Cite
|
Sign up to set email alerts
|

A Full Population Auditing Method Based on Machine Learning

Abstract: As it is urgent to change the traditional audit sampling method that is based on manpower to meet the growing audit demand in the era of big data. This study uses empirical methods to propose a full population auditing method based on machine learning. This method can extend the application scope of the audit to all samples through the self-learning feature of machine learning, which helps to address the dependence on auditors’ personal experience and the audit risks arising from audit sampling. First, this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Their goal was to develop unique sampling methods for improving the performance of machine learning algorithms in solving specific problems (e.g., [3]). Some studies (e.g., [4]) suggested sampling with machine learning in auditing; moreover, only some researchers (e.g., [5]) have indeed implemented machine learning-based sampling in auditing.…”
Section: Of 16mentioning
confidence: 99%
“…Their goal was to develop unique sampling methods for improving the performance of machine learning algorithms in solving specific problems (e.g., [3]). Some studies (e.g., [4]) suggested sampling with machine learning in auditing; moreover, only some researchers (e.g., [5]) have indeed implemented machine learning-based sampling in auditing.…”
Section: Of 16mentioning
confidence: 99%
“…If the purpose is to improve the efficiency of auditing, some published studies (e.g., [5]) integrated machine learning with sampling for detecting anomalies. For example, Chen et al [5] selected the ID3, CART, and C4.5 algorithms to find anomalies in financial transactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the purpose is to improve the efficiency of auditing, some published studies (e.g., [5]) integrated machine learning with sampling for detecting anomalies. For example, Chen et al [5] selected the ID3, CART, and C4.5 algorithms to find anomalies in financial transactions. Their results indicated that a machine learning algorithm can simplify the audit of financial transactions by efficiently exploring their attributes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations